Technological unemployment in the British industrial revolution: the destruction of hand spinning - Schneider, B (University of Oxford, 2023)
This paper analyzes the elimination of hand spinning in Britain during the Industrial Revolution and shows that it was one of the earliest examples of large-scale technological unemployment. First, it uses new empirical evidence and sources to estimate spinning employment before the innovations of the 1760s and 1770s. These estimates reinforce and expand upon the findings of Muldrew (2012): spinning employed up to 20% of women and children by c. 1770. Next, the paper systematically analyzes the course, extent, and locations of technological unemployment produced by mechanization using more than 200 detailed qualitative sources. It first presents an estimate of job loss in hand spinning of cotton by the late 1780s. It then uses evidence from more than 2200 observations by contemporary social commentators, county agricultural surveys, and the 1834 Poor Law Commission’s Rural and Town Queries to show the breadth and duration of unemployment produced by mechanization. The destruction of hand spinning began to impact women and households in the 1780s, and the effects persisted until at least the mid-1830s. Finally, it shows that this technological shock likely had an unequal effect on family incomes that resulted from variation in household composition and local labor market conditions. The findings demonstrate that unemployment must be incorporated into analysis of the impacts of industrialization on living standards and highlight the potential long-run costs of job replacing technology.